Extended Statement by the British Cardiovascular Intervention Society President Regarding Transcatheter Aortic Valve Implantation. Issue 1 (2021) - MacCarthy, Philip; Smith, Dave; Muir, Douglas; Blackman, Daniel; Buch, Mamta; Ludman, Peter; Appleby, Clare; Curzen, Nick; Hildick-Smith, David; Uren, Neal; Turner, Mark; Trivedi, Uday; et al.
No abstract available